2022
DOI: 10.1111/nph.18265
|View full text |Cite
|
Sign up to set email alerts
|

A secreted fungal effector suppresses rice immunity through host histone hypoacetylation

Abstract: Histone acetylation is a critical epigenetic modification that regulates plant immunity. Fungal pathogens secrete effectors that modulate host immunity and facilitate infection, but whether fungal pathogens have evolved effectors that directly target plant histone acetylation remains unknown.Here, we identified a secreted protein, UvSec117, from the rice false smut fungus, Ustilaginoidea virens, as a key effector that can target the rice histone deacetylase OsHDA701 and negatively regulates rice broad-spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 80 publications
0
31
0
Order By: Relevance
“…Ustilago maydis effector Rip1 binds with and re‐localizes the maize lipoxygenase 3 (Zmlox3) from cytosol to the nucleus for suppressing host ROS burst (Saado et al ., 2022). Ustilaginoidea virens effector UvSec117 interacts with and recruits the rice deacetylase OsHDA701 to the nucleus to reduce histone H3K9 acetylation levels, resulting in attenuation of defense gene activation and disease resistance (Chen et al ., 2022). Interestingly, re‐localization of host proteins by effectors may also lead to plant resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Ustilago maydis effector Rip1 binds with and re‐localizes the maize lipoxygenase 3 (Zmlox3) from cytosol to the nucleus for suppressing host ROS burst (Saado et al ., 2022). Ustilaginoidea virens effector UvSec117 interacts with and recruits the rice deacetylase OsHDA701 to the nucleus to reduce histone H3K9 acetylation levels, resulting in attenuation of defense gene activation and disease resistance (Chen et al ., 2022). Interestingly, re‐localization of host proteins by effectors may also lead to plant resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed that the dephosphorylation of OsMPK6 enhanced its stability and inhibited the immunity of rice [ 40 ]. Chen et al [ 54 ] showed that the toxic effect protein UvSec117 of U. virens enters the host cell, interacts with the rice histone deacetylase OsHDA701, and recruits a large amount of OsHDA701 into the nucleus through the nuclear localisation signal of UvSec117. At the same time, the interaction between UvSec117 and OsHDA701 can enhance the deacetylation activity of OsHDA701, reduce the acetylation level of rice histone from two aspects, and then interfere with the activation of defence genes and host immunity.…”
Section: Genetic Mechanism Of the Immune Response To Rfsmentioning
confidence: 99%
“…The geminivirus-encoded protein V2 protein interacts with Nicotiana benthamiana NbHDA6, and competes the NbMET1-NbHDA6 interaction, thus interfering the recruitment of NbMET1 by NbHDA6 to downregulate the TGS-triggered viral DNA genome methylation, which eventually increases host susceptibility to geminivirus infection ( Wang et al, 2018 ). UvSec117, a key effector secreted by Ustilaginoidea virens , targets the rice RPD3-like class HDAC OsHDA701 to the nucleus to reduce H3K9ac and interfer with the activation of H3K9ac-marked defense gene transcription, which eventually promotes pathogen infection ( Chen et al, 2022 ). Overexpression of BcRPD3 in Botrytis cinerea led to a significant decrease in the levels of histones H3 and H4 acetylation at virulence genes, resulting in a slight delay in fungus vegetative growth and infectious structures formation and significantly weakened virulence ( Zhang et al, 2020a ).…”
Section: Histone Modification Regulators Involved In Plant Response T...mentioning
confidence: 99%